Scandex (BD)Limited Standard Operating Procedure of Garments Industry - Khan, Kayoum (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.